Flood Disaster Management On The COVID-19 Pandemic In Sekadau Regency West Kalimantan Province - Ramadhan Pancasilawan; Herijanto Bekti; Muhammad Fedryansyah; Irfan Mauluddin (Universitas Padjadjaran, 2022)
Disaster management began as an emergency response to natural disasters, in the administration of the government's emergency management program there is disaster management. Disaster management describes the initiation of efforts to mitigate, prepare to respond, and recover from disasters. The flood disaster management was hampered in the management of emergency response due non-natural disasters to deal with flood natural disasters during the pandemic COVID-19. This study will discuss in more depth how the flood disaster management that occurred in Sekadau Regency, West Kalimantan Province during the COVID-19 pandemic was carried out by the Sekadau Regency Regional Disaster Management Agency. This research use descriptive qualitative approach. In collecting data, this research uses observation, interviews, literature study, and internet searching. Data collection in this study was carried out with existing studying literature. The author uses a model collaborative capacities in disaster management Allen (2011), namely: Purpose, Structure, Communication, Resources. The emergency management has a weakness, namely the loss of the community's role in the expertise to handle flood natural disasters. The flood disaster that occurred in Sekadau Regency, West Kalimantan Province was caused by high intensity rainfall and the overflowing of the Kapuas River which triggered a flood disaster.